Informed Consent to Psychoanalysis : The Law, the Theory, and the Data - Saks, Elyn R., 1955- (Book collections on Project MUSE., 2013)
"This book examines informed consent to psychoanalysis. It reviews the law. It examines informed consent as a theoretical matter: e.g., is it possible, is it countertherapeutic? It reports on a survey of analysts. The goal is to shed psychoanalytic light on a concept which has changed the delivery of healthcare"--Provided by publisher